2000
DOI: 10.1016/s0002-9440(10)65074-2
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Differentiation of Fetal Liver Epithelial Progenitor Cells after Transplantation into Adult Rat Liver

Abstract: To identify cells that have the ability to proliferate and differentiate into all epithelial components of the liver lobule, we isolated fetal liver epithelial cells (FLEC) from ED 14 Fischer (F) 344 rats and transplanted these cells in conjunction with two-thirds partial hepatectomy into the liver of normal and retrorsine (Rs) treated syngeneic dipeptidyl peptidase IV mutant (DPPIV(-)) F344 rats. Using dual label immunohistochemistry/in situ hybridization, three subpopulations of FLEC were identified: cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(132 citation statements)
references
References 49 publications
6
122
1
3
Order By: Relevance
“…16,17 These findings suggest that Alb þ CK7 þ cells, which have the capacity to give rise to both Alb þ CK7 À and Alb À Ck7 þ progenies, function as hepatic stem/progenitor cells. Therefore, the quantification of Alb þ CK7 þ impotent cells is one of the approaches to evaluate the content of hepatic stem/progenitor cells, although not all Alb þ CK7 þ cells necessarily have the capacity for bipotential differentiation.…”
Section: Resultsmentioning
confidence: 94%
“…16,17 These findings suggest that Alb þ CK7 þ cells, which have the capacity to give rise to both Alb þ CK7 À and Alb À Ck7 þ progenies, function as hepatic stem/progenitor cells. Therefore, the quantification of Alb þ CK7 þ impotent cells is one of the approaches to evaluate the content of hepatic stem/progenitor cells, although not all Alb þ CK7 þ cells necessarily have the capacity for bipotential differentiation.…”
Section: Resultsmentioning
confidence: 94%
“…A small fraction of cells even exhibit bipotential activity and generate both epithelial cell types. 15,17 Fetal liver progenitor cells proliferate extensively in vitro 16 and differentiate into adult parenchymal phenotypes after transplantation into a host animal. 17,25 In the present study we used EGFP-transgenic mice as donors for fetal liver progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 Fetal liver progenitor cells proliferate extensively in vitro 16 and differentiate into adult parenchymal phenotypes after transplantation into a host animal. 17,25 In the present study we used EGFP-transgenic mice as donors for fetal liver progenitor cells. In contrast to other transplantation systems such as the DPPIV rat model, 26 which relies on staining of a developmentally regulated membrane enzyme, all nucleated cells in EGFP mice starting from oocytes constitutively express the fluorogenic transgene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shafritz and colleagues [48] have shown that fetal liver epithelial progenitors (FLEPs) from ED14 rats are more clonogenic than normal adult hepatocytes, for when wild-type FLEPs were injected into recently hepatectomized syngeneic DPPIV-deficient F344 rats they proliferated for at least 6 months and constituted 7% of the recipient liver at this time, compared to colonization of only 0.06% of the liver by wild-type adult hepatocytes. However, much greater colonization of the mutant liver was observed when the recipient rats were given prior administration of retrorsine (a compound whose metabolites form DNA adducts in hepatocytes, preventing them from undergoing DNA replication); at 6 months after transplantation, 60-80% of the recipient liver was occupied by DPPIV + hepatocytes [49]. Important from a human standpoint, such cells can be cryopreserved for up to 20 months with no loss of repopulating activity [50].…”
Section: Mr Alison Et Almentioning
confidence: 99%